The G-protein biased mu-opioid agonist, TRV130, produces reinforcing and antinociceptive effects that are comparable to oxycodone in rats. (1st November 2018) - Austin Zamarripa, C.; Edwards, Shelley R.; Qureshi, Hina N.; Yi, John N.; Blough, Bruce E.; Freeman, Kevin B.
Highlights: TRV130 was compared to oxycodone in self-administration and thermal antinociception. TRV130 produced reinforcing effects that were equipotent to oxycodone. TRV130 produced thermal antinociceptive effects that were equipotent to oxycodone. Abstract: Mu-opioid agonists (e.g., oxycodone) are highly effective therapeutics for pain. However, they also produce reinforcing effects that increase their likelihood of abuse. Recent strategies in drug development have focused on opioids with biased receptor-signaling profiles that favor activation of specific intracellular pathways over others with the aim of increasing therapeutic selectivity. TRV130, a mu agonist biased towards G-protein signaling, produces antinociceptive effects comparable to the mu agonist, morphine, but exhibits reduced side effects. However, in terms of abuse potential, we know of no published preclinical data investigating the effects of TRV130 as a reinforcer. In the present study, we assessed the relative reinforcing effects of TRV130 and oxycodone, a commonly-prescribed mu agonist, in rats self-administering the drugs under a progressive-ratio (PR) schedule of reinforcement. In addition, we assessed the relative potency and efficacy of TRV130 and oxycodone in rats in a test of thermal antinociception (Hot Plate). For self-administration, male Sprague-Dawley rats (n = 7) self-administered intravenous infusions of TRV130 or oxycodone (0.01-0.32 mg/kg/inj) under a PR schedule of reinforcement. For the Hot-Plate test, male rats (n = 7) received subcutaneous injections of TRV130 (0.1–3.2 mg/kg/inj) or oxycodone (0.1–5.6 mg/kg/inj), and nociceptive response latencies were measured. TRV130 and oxycodone were equi-potent and equi-effective in self-administration and thermal antinociception. This study demonstrates that TRV130 produces reinforcing and antinociceptive effects that are quantitatively similar to oxycodone, and that a biased-signaling profile does not necessarily reduce abuse potential.